Juventude, pós-modernidade e declínio da autoridade paterna: visões do cinema contemporâneo - Braghini, Sergio Luis (2011)
The objective of this work is to study the youth, for what it means to pass the family to the social world, and therefore show traces of social change. Our reflections on youth were located in the reading of social scientists, historians, psychoanalysts, and other authors, books, theses and scientific journals in psychology, social sciences and humanities. These readings allowed the path of reflection on the issue of youth in post-modernity and the implications of studies about the decline of the paternal imago, the image that is made of youth. We asked: Is it possible to observe through a historical survey, the decline of paternal authority as to how this idea is presented in the thesis of Jacques Lacan? My hypothesis is that these remains on the decline of paternal authority are recorded in the images of fiction films that demonstrate the social portrait of youth to the present day. To this end, we conducted a film looks back to youth culture between the years 1950 to 2008. It is understood that film is a cultural product registered in a particular historical time partner, is through him that support my thesis. Our hypothesis that the traces on the decline of paternal authority are recorded in the images of fiction films has been confirmed, but not confirmed that there would be a loss of the paternal role, the way Lacan theorized after 1953. What we found in our research is that the decline of symbolic efficacy of the paternal function does not necessarily involve, the decline of paternal authority. We can say that the crisis of legitimacy of authority is no place, because the referential postmodern, as the organizer of great symbolic narrative of this period in capitalism has been the market